PENGARUH STRES KERJA, BEBAN KERJA, LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. JASA MARGA (PERSERO) TBK CABANG BELMERA - Arfi Hafiz Mudrika; Demak Claudia Yosephine Simanjuntak2; Andre Syahputra Tarigan (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
Employee performance can be relied on by several factors that can improve or enhance employee performance. These factors include work stress, excessive workload and a work environment that is not conducive. This study aims to analyze the effect of work stress, workload, and work environment on employee performance at PT. Jasa Marga (Persero) Tbk Belmera Branch. Data were collected from questionnaires from 50 respondents for statistical analysis. The statistical analysis used is descriptive analysis and multiple linear regression analysis. The results showed that Job Stress (X1), Workload (X2) and Work Environment (X3) had a positive and significant effect on Employee Performance (Y) at PT. Jasa Marga (Persero) Tbk, Balmera Branch, Medan, either partially or simultaneously. The findings above illustrate that the company can implement measures to prevent work stress, workload and create a work environment to achieve more optimal employee performance.